Implicit boundary conditions for coupled solvers. (30th May 2018) - Darwish, M.; Mangani, L.; Moukalled, F.
Highlights: A full implicit treatment of boundary conditions its presented. The geometric and physical boundary conditions are treated. The implicit treatment yields extremely good convergence. The explicit treatment is unstable and for the used time step leads to divergence. Abstract: In addition to implicitly resolving the velocity pressure coupling at interior faces, it is also critical for a coupled solver to implicitly resolve this coupling for boundary faces. Failure to account for this leads to substantial degradation in the convergence characteristics of the solver. In this paper, details on the implicit treatment of boundary conditions for a coupled solver are presented in the context of the OpenFOAM ® framework. The boundary conditions presented include two geometric conditions namely, cyclicMMI and symmetry condition and a number of physical boundary conditions (inlet, outlet, and wall). The treatment is illustrated with modification to the boundary element coefficients and its effectiveness demonstrated for the case of "NASA Rotor 37", a standard validation case.